The essence and structure of litigation claim acknowledgement - Qing, Zhao (Civil Procedure Review, 2024)
Acknowledgement refers to the defendant’s recognition of the litigation claim filed by the plaintiff during a judicial proceeding, aiming at concluding the litigation, and changing the right-duty relation between the plaintiff and the defendant from the substantial dimension. Therefore, acknowledgement has dual attributes, litigation act and substantive disposition act. The requirements of establishing the acknowledgement include: the actor of acknowledgement has the ability of litigation act or the agent has the power of agency; acknowledgement does not violate laws, public order and good customs; the object of acknowledgement belongs to the disposable matters of a party; acknowledgement conforms to the requirements for litigation essentials; the intention expressed by the actor for acknowledgement is genuine. The court makes a judgment on acknowledgement in accordance with the defendant’s valid acknowledgement, with the same validity as that of a general judgment; however, there is a difference between their instrument forms. The wrong judgment on acknowledgement may be relieved through appeal or retrial; however, the grounds of relief are only limited to procedural violation or nonconformance of acknowledgement to the requirements for establishment.